2011
DOI: 10.7778/jpkm.2011.25.1.049
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine Promotes Growth of Children

Abstract: ObjectivesThe purpose of this study is to evaluate the effect of the herbal medicine in children's growth.Methods 67 of the children in the age from 3 to 16 were participated in this study(31 of boys and 36 of girls). Department of the pediatrics, ○○ university oriental medical hospital, and the participants were measured their body composition and their bone age, the height percentile of the first and the last visit were measured, and those were compared by the Korean Association of Pediatrics' Growth Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
2
0
1
Order By: Relevance
“…Heredity are important predictors of growth and GH treatment response 13), 21) . However, MPH was not found to be a predictor of response to herbal medicine treatment in the present study; this is in agreement with the results of previous studies on herbal medicine, which reported no influence of heredity on treatment response 6), 7) . The baseline height percentile was also not found to be a predictor of treatment response in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Heredity are important predictors of growth and GH treatment response 13), 21) . However, MPH was not found to be a predictor of response to herbal medicine treatment in the present study; this is in agreement with the results of previous studies on herbal medicine, which reported no influence of heredity on treatment response 6), 7) . The baseline height percentile was also not found to be a predictor of treatment response in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…However, whether baseline percentile is a determinant of treatment response with herbal medicine is a matter of controversy [6][7][8][9] . In a previous study, GH therapy was reported as being effective in children of the lower percentile group 30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…이 등 13) , 박 14) , 정 등 15) , 조 등 16) , 유 등 17) , 정 등 18) , 박 등 19) , 이 등 20) , 윤 등 체성분 분석을 이용한 연구는 김 등 24) , 홍 등 25) , 김 등 Ⅲ. Results (Table 7).…”
Section: )unclassified